2004
DOI: 10.1152/ajpcell.00334.2003
|View full text |Cite
|
Sign up to set email alerts
|

Polymodal regulation of hTREK1 by pH, arachidonic acid, and hypoxia: physiological impact in acidosis and alkalosis

Abstract: Miller, Paula, Chris Peers, and Paul J. Kemp. Polymodal regulation of hTREK1 by pH, arachidonic acid, and hypoxia: physiological impact in acidosis and alkalosis. Am J Physiol Cell Physiol 286: C272-C282, 2004. First published October 1, 2003 10.1152/ ajpcell.00334.2003.-Expression of the human tandem P domain K ϩ channel, hTREK1, is limited almost exclusively to the central nervous system, where ambient PO 2 can be as low as 20 Torr. We have previously shown that this level of hypoxia evokes a maximal inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 24 publications
2
36
4
Order By: Relevance
“…IIIC6). Although the relevance of the above conclusions has been questioned by reports which suggested that TREK current is not stimulated under hypoxic conditions (235,236), the effect of PUFA on TREK was repeatedly corroborated by other studies (35,44).…”
Section: Neuroprotection By Pufamentioning
confidence: 74%
“…IIIC6). Although the relevance of the above conclusions has been questioned by reports which suggested that TREK current is not stimulated under hypoxic conditions (235,236), the effect of PUFA on TREK was repeatedly corroborated by other studies (35,44).…”
Section: Neuroprotection By Pufamentioning
confidence: 74%
“…Therefore, l-NBP-mediated inhibition of TREK-1 channels may help to maintain or increase the function of glutamate uptake by astrocytes during brain ischemia. Furthermore, the TREK-1 channel is known to be an O 2 -sensitive K + channel, and acute hypoxia can occlude its activation by AA and other activators [38,39] . This finding suggests that TREK-1 may not be activated during systemic hypoxia (as occurs during cerebral ischemia).…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al (2003) reported that acute hypoxia occluded human TREK-1 expressed in the HEK293 cells under ischemic and/or acidotic conditions. Furthermore, it is reported that inhibited TREK-1 current by intracellular alkanization was further suppressed by hypoxia (Miller et al 2004). On the contrary, other reports demonstrated that TREK-1 was not oxygen sensitive (Buckler and Honore 2005;Caley et al 2005).…”
Section: Introductionmentioning
confidence: 96%